Three new species of the spider family Pholcidae (Arachnida: Araneae) from Taita-Taveta, Kenya - Yao, Zhiyuan; Kioko, Grace M.; Kioko, Esther N.; Li, Shuqiang (Zootaxa, 2019)
Only nine species of the spider family Pholcidae C.L. Koch, 1850 are endemic in Kenya. In this study, three new species from Taita-Taveta County, southern Kenya are reported. They belong to two genera of the pholcid spiders: Buitinga qingyuani Yao & Li sp. nov. (male, female), B. wamitii Yao & Li sp. nov. (male), and Smeringopus voi Yao & Li sp. nov. (male, female). All material studied is deposited in the National Museums of Kenya (NMK) in Nairobi, Kenya.